資訊融入生物科教學之教材製作與教學策略初探 | An Exploratory Study of Integrating Information and Communication Technology into Biology Instruction in Junior High School: Curriculum and Pedagogy - 張梅鳳 Mei-Feng Chang (Tushuguanxue yu Zixun Kexue, 2004)
頁次：55-65